Humanist Concept in Settlement of Non-Performing Murabahah Financing - Fu'aida Nur Hikmawati; Muh. Nashirudin (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This research examines the process of resolving Non-Performing Murabahah financing, and how the Fatwa of the National Sharia Council (DSN) of the Indonesian Ulema Council (MUI) reviews the Settlement of Non-Performing Finance at Saving and Loan Association and Sharia Financing (KSPPS) Bayt al-Māl wa al-Tamwīl (BMT) Sakinah Mojolaban, Sukoharjo. This research is field qualitative research. The research results show that efforts to handle problematic murabahah financing carried out by BMT are by providing gradual administrative warnings, restructuring financing, rescheduling or other policies that apply at BMT. If the customer is unable to fulfill his obligations, BTM will auction off the customer's collateral. BMT also offers the option of contract conversion by creating a new contract for customers who cannot complete murabahah financing in accordance with the provisions of the Fatwa of the DSN-MUI No. 49/DSN-MUI/II/2005 Concerning Murabahah Contract Conversion. This effort was made to save BMT assets by applying Islamic and humanitarian values.